COVID-19 opens up domestic market for Indian shrimp - Krishnan, M.; Babu, Suresh Chandra (Elsevier, 2022)
COVID-19 pandemic presents both a challenge and an opportunity to the Indian shrimp sector. With revitalizing the institutional arrangements and redirecting the focus, the Indian shrimp industry can flourish just by adapting to the needs of the local demand, even when the export prospects are uncertain. This paper takes a historical perspective of Indian shrimp farming and exports and suggests a domestic alternative/supplementary market for Indian farmed shrimp, resulting from COVID-19.